Maksimalisasi Laba Umkm Pada Pasca Pandemi Dalam Pembiayaan Perbankan Syariah - Abdillah, Bacharuddin; Yazid, Muhammad (ITB AAS INDONESIA Surakarta, 2023)
Profit maximization in an Islamic perspective really needs to be applied to companies, especially SMEs. The purpose of this study is to find out how to maximize MSME profits in the midst of a pandemic based on the point of view of Islamic Economics. Islamic economics is also an action-taking system that describes all phenomena based on Islamic morals and ethics. Then, to achieve this goal, library research or library research methods from various journals are used. The results of the study conclude that the maximization of MSME profits during the pandemic can be done by paying attention to the main points of the rules in Islam. Such as establishing good relationships, ensuring that the products sold are halal and safe, as well as innovating and being creative.